INTERACTIVE TEACHING METHODS IN THE PROCESS OF STUDYING PSYCHOLOGICAL DISCIPLINES - Черушева, Галина (Modern engineering and innovative technologies, 2024)
The article substantiates the relevance of psychological knowledge in the system of management activities. The search for ways to effectively develop an organization requires managers to realize the role of psychological factors of management, a deep unde